Effect of Stichopus Hermanni to Bigonial Width on Maxillary Suture Expansion using Cephalometric Analysis - Kristin Gaby Rosari; Noengki Prameswari; Lisdiana Mardanus (Denta Journal Kedokteran Gigi, 2017)
Background:Maxillary expansion uses mechanical forces to open the maxillary suture which causes inflammation and bone remodeling around the area. Stichopus hermanni is known to contain flavonoid, chondroitin sulfate, and saponin which is used to inhibit inflammatory process, increase bone metabolism and mineralization, and wound healing. Purpose: The aim of this experiment is to know the effect of Stichopus hermanni to bigonial width on maxillary suture remodeling expansion using cephalometric analysis. Materials and Methods: Experimental units used were 24 male Cavia cobaya divided into 4 groups (n=6). Group K(-) is negative control. Helical spring was applied and activated in the other 3 groups for 10 days. Group K(+) was given 2% NaCMC gel, both group P1 and P2 was given 3% Stichopus hermanni gel. Group P2 were also given retention period for 10 days after activation period. Cavia cobaya were then decapitated and observed for the bigonial width changes. The data was analyzed with One Way ANOVA test continued with LSD test. Results: The result of ANOVA test showed siginficant differences among the treatment groups p=0,000 (p<0,05). LSD test showed significant differences between group K(-) and K(+) (Sig. 0,005), K(-) and P1 (Sig. 0,001), and group K(-) and P2 (Sig. 0,000). Conclusion: 3% Stichopus hermanni gel increases bigonial width but not significant in remodeling process on maxillary suture expansion.